THE IMPORTANCE OF NATIONAL CULTURE STUDIES IN THE ORGANIZATIONAL CONTEXT - Edlira Gjuraj (Tukaj) (European Scientific Journal, ESJ, 2013)
Cultural problems have not become so apparent and delicate, for the world, today only. They have drawn the interest of many researchers for many years, bringing about the realization of many important studies, in size and scope, as well as in a representative capacity and actuality of (their) results. But, even though many researchers accept the influence of culture in organizational values and attitudes they very rarely go as far as to empirically confirm these relations.Does national culture need to be specially considered and studied at organizational studies in Albania?Everyone in the organization aims to achieve individual goals through the achievement of organizational goals. The continuous growth and expansion of our businesses abroad (meaning subsidiaries or departments of the Albanian companies abroad, because with respect to Row Materials or Final Product markets there are early signs of internationalism) increases the importance of intercultural management. This starts, first of all, with a thorough understanding of national culture and the impact culture plays in values and attitudes toward work. Moreover, our culture, starting from some of its components (such as language, origin,…) or even the historical factors that have influenced it, is distinct, or better say we are used to see it as special or unique, seeing ourselves as separated and isolated from the rest of the world. The article aims to theoretically analyze the importance national cultural studies have in a good examination of organizational problems in Albania.